Volume 13 Number 1 2017
DOI: 10.18057/ijasc.2017.13.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Tie Bar Effects on Structural Behavior of Suspended Scaffolding Systems

Abstract: ABSTRACT:The collapse of scaffolds can bring about substantial damage and economic loss. In recent years, over hundreds of people died and an even greater number have been injured because of inadequate scaffolding system designs. In this study, the effects of truss height and number of tie bars on the structural behavior of suspended scaffolding systems were experimentally investigated. Three full-scale scaffolding systems with truss heights of 30, 45, and 60 cm were tested in the laboratory. Each system inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The choice of this equipment must consider the weather conditions (namely the action of the wind) and the characteristics of the roof. By comparison with the supported scaffolds, the assembly and disassembly times are shorter, it has a good carrying capacity for people and materials, and it allows access to façades with restrictions at the soil level [19], but it has limitations in complex features and protrusions from the façade [2].…”
Section: Suspended Scaffoldsmentioning
confidence: 99%
“…The choice of this equipment must consider the weather conditions (namely the action of the wind) and the characteristics of the roof. By comparison with the supported scaffolds, the assembly and disassembly times are shorter, it has a good carrying capacity for people and materials, and it allows access to façades with restrictions at the soil level [19], but it has limitations in complex features and protrusions from the façade [2].…”
Section: Suspended Scaffoldsmentioning
confidence: 99%
“…Yu et al [26] and Chu et al [27] integrated the lowest eigenmode with a column out-of-straightness magnitude of 1/1000 for the height of the scaffold units into the model. Sevim et al [28] investigated the effects of truss height and number of tie bars on the structural behavior of suspended scaffolding systems through experiments, the results showed that a scaffolding system with 60 cm-high truss and two tie bars presents optimal safety and cost-savings. Liu et al [29] presented a mortise-tenon steel-tube scaffold, the influencing laws of storey height, vertical member interval and other factors were determined through parameter analysis, research results provide important references for future in-depth studies and engineering applications of the mortise-tenon steel-tube scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Among other configurations of scaffolding, Sevim et al investigated the structural behavior of tie-bar numbers on the suspended scaffolding systems in the laboratory. In this study, they tested fifteen suspended scaffolding systems and obtained the load-displacement curves; particularly, the optimal suspended scaffolding system in terms of safety and cost was determined [9].…”
Section: Introductionmentioning
confidence: 99%